Living Aik: Lived Pedagogy, Moral Formation, And Everyday Islamic Learning In Indonesian Modernist Muslim Higher Education - Gita Danu Pranata; Talqis Nurdiyanto; Askuri; Ahmad Zaki An-Nafiri (International Journal of Educational Research & Social Sciences, 2026)
This article examines Al-Islam and Kemuhammadiyahan (AIK) as a lived pedagogical process in Muhammadiyah and ‘Aisyiyah higher education in Yogyakarta, Indonesia. Rather than approaching AIK only as a compulsory curriculum or an institutional instrument for transmitting Muhammadiyah values, the article analyzes how AIK is experienced, embodied, negotiated, and sometimes contested in everyday university life. Based on in-depth interviews with nineteen students, AIK lecturers, and institutional actors involved in AIK coordination at Universitas Muhammadiyah Yogyakarta, Universitas Ahmad Dahlan, and Universitas ‘Aisyiyah Yogyakarta, the article shows that AIK operates through three interconnected dimensions: classroom pedagogy, embodied pedagogy, and institutional pedagogy. Students encounter AIK through lectures, discussions, worship practices, Qur’anic recitation, Al-Ma’un projects, campus mosques, Baitul Arqam, LazisMu, student organizations, and digital religious media. The findings demonstrate that students do not simply receive AIK as fixed knowledge. They interpret it through prior religious backgrounds, bodily habits, family traditions, institutional expectations, and personal aspirations. For some students, AIK deepens religious understanding and social empathy; for others, it raises questions about authority, ritual difference, and religious standardization. The article argues that AIK is best understood as lived pedagogy: a field of Islamic learning in which students learn, embody, negotiate, and sometimes contest Muhammadiyah values in concrete social worlds.